Penggunaan Konsentrat hijau untuk Meningkatkan Produksi Ternak Kelinci New Zealand White - Eko Marhaeniyanto; Sri Susanti (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2017)
The in-vivo experimental study on rabbit animals  mixed of Moringa oleifera, Lamk(MOL), Gliricidia sepium, Paraserianthes falcataria and Ceiba pentandra leaf meal(1: 1: 1: 1 ratio) of 10%, 20% and 30% in concentrate feed (= green concentrate).The research was conducted at "Mandiri" Breeders Association, Kagrengan NgijoKarangploso. The research aimed to evaluate the use of green concentrate withforage of cabbage leaves on feed intake, digestibility, digestible intake and averagedaily gain (ADG) of rabbit. The method used was the experimental method, arrangedin Randomized Block Design (RBD) with 4 treatments and 4 groups. The treatmentsapplied were P0 (basal diet+concentrate 18% crude protein/CP, without leaf meal),P1 (basal diet+green concentrate 18%CP with 10% mixed leaf meal), P2 (basaldiet+green concentrate 18%CP with 20% mixed leaf meal), P3 (basal diet+greenconcentrate 18%CP with 30% mixed leaf meal). The measured variables were feedintake, digestibility, digestible intake and average daily gain of rabbit.The resultsshowed that the use of 10 to 30% mixed leaf meal in green concentrate of rabbitsprovide to produce ADG higher than concentrate without leaf meal. During the study,rabbit’s body weight increased to 1.8-2.3 kg head-1. Supplementation of mixed leafmeal up to 30% on green concentrate can produce feed intake of 4-5% dry matter(DM) from  body weight, and ADG up to 19.83 ± 7.21 g head-1day-1